Plasma osteopontin may predict neuroinflammation and the severity of pediatric traumatic brain injury. Issue 1 (January 2020) - Gao, Ning; Zhang-Brotzge, Xiaohui; Wali, Bushra; Sayeed, Iqbal; Chern, Joshua J; Blackwell, Laura S; Kuan, Chia-Yi; Reisner, Andrew
Traumatic brain injury (TBI) is the leading cause of death in children and adolescents in developed countries, but there are no blood-based biomarkers to support the diagnosis or prognosis of pediatric TBI to-date. Here we report that the plasma levels of osteopontin (OPN), a phosphoprotein chiefly secreted by macrophages and/or activated microglia, may contribute to this goal. In animal models of TBI, while OPN, fibrillary acidic protein (GFAP), and matrix metalloproteinase 9 (MMP-9) were all readily induced by controlled cortical impact in the brains of one-month-old mice, only OPN and GFAP ascended in the blood in correlation with high neurological severity scores (NSS). In children with TBI (three to nine years of age, n = 66), the plasma levels of OPN, but not GFAP, correlated with severe TBI (Glasgow Coma Score ≤ 8) and intracranial lesions at emergency department. In addition, the plasma OPN levels in severe pediatric TBI patients continued to ascend for 72 h and correlated with mortality and the days requiring ventilator or intensive care unit support, whereas the plasma GFAP levels lacked these properties. Together, these results suggest that plasma OPN outperforms GFAP and may be a neuroinflammation-based diagnostic and prognostic biomarker in pediatric TBI.